DESIGN AND OPTIMIZATION OF MILLING MULTI TIP CUTTER BY VARYING DEPTH PARAMETERS (International Journal of Food and Nutritional Sciences, 2022)
One of the most important factors when cutting toughened materials is surface accuracy. Practical experience is typically necessary for setting the parameters of CNC machining operations. Sometimes, trial and error is even used to choose the settings, which increases the cost of the instrument and the production time. The number of cutting tool tips that are used in the cutter will result in an increase in surface finish; surface finish and tool wear are also correlated with the depth of cut. The depth of cut determines how complicated a specific tool design needs to be in order to machine complex profiles with a good surface quality. The two types of tools that are discussed in this work are the four flute bull nose cutter and the multi tip facing cutter. Surface finish will be compared and the differentiation in variable depth of cut with constant feed and speed in both situations will be optimised. With 4-tip cutters, the MEKINO 3-axis VMC was utilised for the experimental evaluation, and its parameters were optimised to improve surface finish.